2018
DOI: 10.3389/fpsyt.2018.00166
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Correlates in Internet Gaming Disorder: A Systematic Literature Review

Abstract: Internet Gaming Disorder (IGD) is a potential mental disorder currently included in the third section of the latest (fifth) edition of the Diagnostic and Statistical Manual for Mental Disorders (DSM-5) as a condition that requires additional research to be included in the main manual. Although research efforts in the area have increased, there is a continuing debate about the respective criteria to use as well as the status of the condition as mental health concern. Rather than using diagnostic criteria which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
2
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 209 publications
(141 citation statements)
references
References 73 publications
7
124
2
8
Order By: Relevance
“…Despite these different terminologies used, internet-related disorders have received growing research interest and require further investigation. Indeed, many studies have explored internet-related addiction from different aspects, such as epidemiological studies, comorbidity studies, neuroimaging studies, intervention and treatment studies (e.g., Kuss et al, 2014;Kuss, Pontes & Griffiths, 2018;Shek & Leung, 2013;Shek & Yu, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Despite these different terminologies used, internet-related disorders have received growing research interest and require further investigation. Indeed, many studies have explored internet-related addiction from different aspects, such as epidemiological studies, comorbidity studies, neuroimaging studies, intervention and treatment studies (e.g., Kuss et al, 2014;Kuss, Pontes & Griffiths, 2018;Shek & Leung, 2013;Shek & Yu, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…There is increasing evidence that, in its extreme, excessive media usage can also lead to behavioral addiction, This seems to be particularly the case for internet gaming. Studies examining the neuronal consequences of internet gaming disorder reported numerous significant changes (99,100), including alterations in resting-state EEG coherence (101), significant alterations in cortical thickness (102,103), altered functional connectivity in the default mode network (104,105), and significant associations with ADHD and other psychiatric disorders (106,107). As they now stand, these findings are correlational and cannot establish causation.…”
Section: Studying the Effects Of Media Overusementioning
confidence: 99%
“…Overall, the rapid growth of OG has been interwoven with uncertainties about which populations are primarily engaged, and OG's effect on well being (Anderson et al 2017;Kuss and Griffiths 2012;Pontes et al 2017a;Stavropoulos et al 2018b). Despite OG having many positive psychosocial effects 1 beyond satisfying one's leisure needs Carras et al 2018;Jones et al 2014), for excessive gamers, psychosocial repercussions can be multiple, 2 compromising their concurrent and future adaptation (Anderson et al 2017;Beard et al 2017;Kuss and Griffiths 2012;Kuss et al 2017;Pontes et al 2017b;Kuss et al 2018;Stavropoulos et al 2018aStavropoulos et al , 2018bStavropoulos et al 2019). The extent and the significance of the excessive OG's negative repercussions have prompted questions and concerns regarding its classification as a distinct psychopathological entity and its inclusion in the broader category of addictive behaviors 3 (Kuss et al 2018;Hu et al 2018;Scerri et al 2018).…”
mentioning
confidence: 99%